Influence of Glomus Mossease and Nitrogen Fertilization on Growth and Yield of Sweet Potato (Ipomoea Batatas L. ) - Ahmed, Yassin Mohamed (2005)
Application of arbuscular mycorrhizae (AM) in sweet potato production can contribute to reduction of input of chemical fertilizers in a sustainable agriculture. Pot and field experiments were conducted to determine the effect of AM inoculum level, and AM inoculation with different rates of nitrogen, on growth and yield of sweet potato. A pot experiment was conducted under glasshouse conditions using Sepang Oren sweetpotato cultivar grown in unsterilized Bungor series soil, and inoculated with 0, 20, 40 and 80 g plant-' of AM inoculum, consisting of Glornus mosseae UK118. The soil was amended with organic compost JITU Biofertilizer 03 at rate of 20 t ha", and inorganic fertilizer N, P, and K at the rate of 30 kg N, 60 kg PzOs and 100 kg K20 ha-', respectively. Results showed that AM inoculum level significantly (p<0.05) influenced the root colonization, but not the storage root yield. Application of 40 g plant-' G. mosseae inoculum significantly increased the root infection, spore number and P concentration in shoot. Different levels of AM applied showed no significant difference on storage root yield, starch content and nutrient concentrations. A field experiment was conducted to assess the effect of AM inoculation and nitrogen fertilization rates on growth and yield of sweetpotato. Experimental plots were prepared in the UPM Integrated Farm and three levels of nitrogen fertilizer used were 0,60 and 120 kg ha-' in the form of urea in combination with two levels of AM inoculation. Inorganic fertilizers were applied at the rate of 60 kg P2O5 and 100 kg K20 ha-'. Sweetpotato was harvested at 120 days of growth. Results showed that application of nitrogen significantly (P<0.05) influenced the yield of sweetpotato. Storage root yield increased with increasing nitrogen fertilizer, and application of 60 kg N ha-' and 120 kg N ha-' showed storage roots yield increase of 54.1% and 83.6% respectively, compared to control treatment. The present study showed no significant effect of G. mosseae on sweetptoato yield, plant nutrient uptake and soil nutrient concentrations. However, the mycorrhizal inoculation significantly (pC0.05) influenced the root colonization and AM spore number in the soil. The highest root colonization of 44.36% was in AM inoculated plant with 120 kg N ha-' fertilization rate. The highest spore number of 46 spore 10 g-' soil was observed in AM inoculated treatment without N fertilization.